PERAN TOKOH AGAMA SEBAGAI MOTIVATOR DALAM PENINGKATAN KEPARIWISATAAN - Bonaparte Priyatna (Dialektika, 2017)
Human mobility is now faster both intra-country and internationally, people are also increasingly have spare time that can be used to find relaxation, pleasure or add insight. Tourism activities involve social life and social interaction between the traveler with the beneficiaries wistawan very influential on the development of tourism. The better the interaction between tourists with a receptive community faster development of tourism. All of this will contribute to increased economic growth and living standards and social welfare. The religious leaders as an opinion leader must necessarily be concerned with his own credibility in the eyes of his people and the people around him. Right now there is growing religious tourism that is kunjugan to a place of worship and pilgrimage tourism.